Sowiecka propaganda i orientalizujące stereotypy podczas „Wielkiej Wojny Ojczyźnianej”. Casus Uzbeków w obwodzie kirowskim - Rohoziński, Jerzy (1971– ) (Instytut Historii im. Tadeusza Manteuffla Polskiej Akademii Nauk, 2024)
The article analyses the historical context of archival documents from the second half of 1943. These documents reveal traces of conspiracy theories suggesting that Uzbek workers mobilised to the rear of the front were allegedly trading their food rations.
p. 67-82
Summary in English and Russian.
Keywords: Soviet military propaganda; Soviet “Friendship of Nations”; “Great Patriotic War” mythology; stereotyping Central Asians; “imagined community” of the Soviet Union; Soviet Union - ethnic relations - history; minorities - government policy - Soviet Union; Muslims - Soviet Union; Communism and Islam; Asia, Central - social conditions - 1917-1991; Muslims - Asia, Central - social conditions - 20th century; World War, 1939-1945 - Soviet Union; propaganda - Soviet - history